IMPLEMENTASI PRINSIP RETORIKA DALAM NASKAH PIDATO SISWA KELAS IX SMPN 7 SINGARAJA - Sang Ayu Putu Nilayani .; Drs. I Nyoman Merdhana, M.Pd .; Ida Ayu Made Darmayanti, S.Pd. . (Jurnal Pendidikan Bahasa dan Sastra Indonesia Undiksha, 2014)
Penelitian ini bertujuan (1) mendeskripsikan kesatuan dalam naskah pidato siswa kelas IX SMPN 7 Singaraja, (2) mendeskripsikan kekoherenan dalam naskah pidato siswa kelas IX SMPN 7 Singaraja, (3) mendeskripsikan kevariasian dalam naskah pidato siswa kelas IX SMPN 7 Singaraja, (4) mendeskripsikan kepenekanan dalam naskah pidato siswa kelas IX SMPN 7 Singaraja, dan (5) mendeskripsikan kepararelan dalam naskah pidato siswa kelas IX SMPN 7 Singaraja. Subjek penelitian ini adalah siswa kelas IX SMPN 7 SIngaraja. Objek penelitian ini adalah prinsip retorika dalam naskah pidato yang meliputi: kesatuan, kekoherenan, kevariasian, kepenekanan, dan kepararelan. Metode pengumpulan data yang digunakan adalah metode dokumentasi. Data yang diperoleh dianalisis dengan menggunakan teknik analisis deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa (1) penggunaan kesatuan dalam naskah pidato adalah sebanyak 96 dari 110 paragraf yang diteliti. Penggunaan ditandai oleh adanya satu ide pokok kemudian diikuti oleh beberapa kalimat penunjang; (2) penggunaan kekoherenan dalam naskah pidato adalah sebanyak 108 dari 110 paragraf yang diteliti. Penggunaan kekoherenan ditandai oleh adanya hubungan yang erat antarkalimat dalam paragraf; (3) penggunaan kevariasian dalam naskah pidato adalah sebanyak 110 dari 110 paragraf yang diteliti. Penggunaan kevariasian ditandai oleh adanya variasi jenis kalimat dan variasi bentuk kalimat; (4) penggunaan kepenekanan dalam naskah pidato adalah sebanyak 93 dari 110 paragraf yang diteliti. Penggunaan kepenekanan ini ditandai oleh adanya penggunaan urutan kata, tingkatan bagian-bagian kalimat, pengulangan kata, dan penggunaan susunan inversi; dan (5) penggunaan kepararelan dalam naskah pidato sebanyak 82 dari 110 paragraf yang diteliti. Penggunaan tersebut ditandai oleh adanya penggunaan kesejajaran bentuk. Kata Kunci : Prinsip Retorika dan Naskah Pidato This research aimed to ( 1 ) describe the speech manuscript unity of ninth grade student in SMP 7 Singaraja , ( 2 ) describe the speech manuscript coherence of ninth grade student in SMP 7 Singaraja , ( 3 ) describe the speech manuscript variation of ninth grade student in SMP 7 Singaraja , ( 4 ) describe the speech manuscript stressing of student speech ninth grade student in SMP 7 Singaraja , and ( 5 ) describe the speech manuscript parallel of student speech ninth grade student in SMP 7 Singaraja . The subjects were students of ninth grade student in SMP 7 Singaraja . This study was the principle object of rhetoric in speeches that include: unity, coherence, variation , stressing , and parallel . The data collection method used is the method of documentation. The data obtained were analyzed using qualitative descriptive analysis techniques. The results of this study indicated that (1) the use of the unity of the speech manuscript is as much as 96 of the 110 paragraphs which were studied. The use was marked by the existence of a main idea followed by some supporting sentences; (2) the use of coherence the speech manuscript is as much as 108 of the 110 paragraphs which were studied. The use of coherence was marked by the existence of close relationship between sentences in a paragraph ; ( 3 ) the use of variation the speech manuscript is as many as 110 of the 110 paragraphs which were studied . The use of variation is marked by the existence of sentence types variation and sentence forms variation ; ( 4 ) the use of stressing in speech manuscript is as many as 93 of the 110 paragraphs which were studied . The use of this stressing was marked by the use of word order , parts of a sentence level , word repetition , and the use of the composition of the inversion ; and ( 5 ) The use of parallel in speech manuscript is as much as 82 of 110 paragraphs which were studied . The use is marked by the use of alignment shapes . keyword : rhetoric and speech manuscript